High-level production of functional muscle alpha-tropomyosin in Pichia pastoris - Hilario, E.; Lataro, R. C.; Alegria, M. C.; Lavarda, SCS; Ferro, J. A.; Bertolini, Maria Celia [UNESP] (Academic Press Inc., 2001)
Although numerous studies have reported the production of skeletal muscle alpha -tropomyosin in E. coli, the protein needs to be modified at the amino terminus in order to be active. Without these modifications the protein does not bind to actin, does not exhibit head-to-tail polymerization, and does not inhibit the actomyosin Mg2+-ATPase in the absence of troponin. on the other hand, the protein produced in insect cells using baculovirus as an expression vector (Urbancikova, M., and Hitchcock-DeGregori, S. E., J. Biol. Chem., 269, 24310-24315, 1994) is only partially acetylated at its amino terminal and therefore is not totally functional. In an attempt to produce an unmodified functional recombinant muscle alpha -tropomyosin for structure-function correlation studies we have expressed the chicken skeletal alpha -tropomyosin cDNA in the yeast Pichia pastoris. Recombinant protein was produced at a high level (20 mg/L) and was similar to the wild type muscle protein in its ability to polymerize, to bind to actin and to regulate the actomyosin S1 Mg2+-ATPase. (C) 2001 Academic Press.
Keywords: alpha-tropomyosin; recombinant protein; Pichia pastoris